Challenging Goliath. Informal Unionism and Digital Platforms in the Food Delivery Sector. The Case of Riders Union Bologna - Marrone, Marco; Finotto, Vladi (PARTECIPAZIONE E CONFLITTO, 2019)
The growth of digital platforms in many industries attracted the attention of scholars and activists alike. A number of studies, in disciplines such as management, emphasized the role of digital technology in transforming market logics and described platforms as the harbingers of a more democratic organization of economic activities. The more platforms became relevant in intermediating between clients and providers of services and goods, the more conflicts related to working conditions rose, calling for a critical approach to the so-called platform economy. The most recent debate focused on the connection between the rise of platforms and the effects of neoliberalism in relaxing employment regulations and in pushing an increasing number of individuals towards "gig" types of jobs. We deal with these tensions and consider the emerging forms of organization and strategies of workers’ movements. We focus on the food delivery sector and on the most popular informal workers’ movement in Italy: Riders Union Bologna (Rub). The aim of the paper is to investigate the factors that stimulated the rise of informal unionism in food delivery, and to pinpoint the reasons motivating specific struggling and organizing strategies among platform workers.